ANALYSIS OF FACTORS RELATED TO THE SEVERITY OF COVID 19 AT TADJUDDIN CHALID HOSPITAL MAKASSAR - Yuliana Syam; Abdul Majid; Andri Prianto; Basri Syam (Universitas Islam Negeri Alauddin Makassar, 2023)
Background: Covid 19 is a disease caused by a new coronavirus. This virus can be transmitted from human to human and has spread widely in China and more than 190 countries. Mild symptoms of Covid 19 include runny nose, sore throat, cough, and fever. The occurrence of arterial hypoxemia which causes the main feature of respiratory distress in Covid 19. Death due to Covid 19 in Indonesia itself is dominated by infected patients who have comorbidities such as hypertension, diabetes, cardiovascular disease or respiratory disease can also greatly affect the prognosis of Covid 19. Objective: This study aims to determine the relationship between age, gender, education level, and history of comorbidities with the severity of covid 19. Method: This research is a quantitative study using observational analytic with a cross sectional study design. The population in this study were all confirmed Covid 19 patients who were treated from April 2020 to 2021. The sampling technique was the total sample. Result: The results showed that the relationship between age and severity of Covid 19 was obtained with p value = 0.010, for gender p value = 0.111, then for education level, p value = 0.005, and for comorbidities, p value = 0.000. Conclusion: There is a relationship between age, education level and comorbidities with the severity of Covid 19. Further research is expected to find other factors such as lifestyle, environment and adherence in undergoing treatment to the severity of Covid 19.